A Review on Types and Treatment Strategies of Severe Combined Immunodeficiency - Dhomakonda , Bhavani; Sireesha , Vankodoth; Shirisha , Boddu; Sushma , Gadila; Sai Charitha , Mekala; Rama Rao , T. (Journal of Drug Delivery and Therapeutics, 2025)
Severe Combined Immunodeficiency (SCID) is a rare and life-threatening congenital disorder affecting the immune system's functionality due to mutations in crucial genes involved in immune cell development. This review provides a comprehensive overview of SCID, covering its genetic basis, immune system components, clinical manifestations, diagnostic methods, and treatment strategies. The review emphasizes the importance of early detection through newborn screening, enabling prompt treatment and enhancing survival rates for individuals with SCID. SCID can be classified as Typical, Atypical which also includes Omenn Syndrome, atypical/leaky, variant. Gene mutations with various severe infections, diarrhea, lack of T cells, reduction in naive T cells, increase in T cells and absence of proliferative responses to mitogens, or T cells with a maternal ancestry are all characteristics of typical SCID. About a dozen genes, which together make up the rare genetic condition SCID, are chiefly responsible for its X-linked or autosomal recessive inheritance. Due to infrequent incidences, early detection and treatment may go unnoticed. CD3+ > 300 cells/L and a diminished, but discernible, proliferative response to PHA (>10-30% of the control) are characteristics of atypical SCID. Other names for it include "leaky SCID”. When there is no known gene issue and there are still 300–1500 T cells per liter with reduced function, variant SCID is diagnosed. The treatment options available to treat SCID are bone marrow transplantation also known as hematopoietic stem cell transplant (HSCT), gene therapy, enzyme replacement therapy, gamma globulins etc. The most widely used treatment with a high success rate is bone marrow transplantation (BMT), which can enable the body to once again create those vital infection-fighting cells. Blood cell production occurs in the bone marrow. Most SCID children pass away before they are two without a BMT.Keywords: Bubble boy disease, gene therapy, hematopoietic stem cell transplantation (HSCT), bone marrow transplantation (BMT), Enzyme replacement therapy (ERT).